2013
DOI: 10.1113/expphysiol.2012.070524
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal hormone deprivation affects macrophage catecholamine metabolism and β2‐adrenoceptor density, but not propranolol stimulation of tumour necrosis factor‐α production

Abstract: New Findings r What is the central question of this study?Glucocorticoids modulate extraglandular catecholamine metabolism and adrenoceptor expression in many cell types. Catecholamines modulate the production of inflammatory mediators by macrophages. It was hypothesized that adrenal hormones affect tumour necrosis factor-α production in rat macrophages by altering the autocrine/paracrine action of catecholamines. r What is the main finding and its importance?In rat macrophages, adrenalectomy increased tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Inhibition of the β-adrenergic receptor with the β-blocker propranolol, or depletion of adrenal catecholamines by adrenalectomy, led to increased LPS-induced tumor necrosis factor (TNF) α production in peritoneal macrophages [12]. Alveolar macrophages recovered from mice chronically treated with β-blockers produced more noradrenaline, interleukin (IL) 6 and TNFα following LPS treatment ex vivo [13].…”
Section: Catecholaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the β-adrenergic receptor with the β-blocker propranolol, or depletion of adrenal catecholamines by adrenalectomy, led to increased LPS-induced tumor necrosis factor (TNF) α production in peritoneal macrophages [12]. Alveolar macrophages recovered from mice chronically treated with β-blockers produced more noradrenaline, interleukin (IL) 6 and TNFα following LPS treatment ex vivo [13].…”
Section: Catecholaminesmentioning
confidence: 99%
“…Recent data suggest that catecholamines can auto-regulate their levels and function by controlling expression of both tyrosine hydroxylase as well as catecholamine receptors [12]. For instance, adrenal catecholamines contribute to the paracrine regulation of macrophage synthesis of catecholamines and expression of the β-adrenergic receptor.…”
Section: Catecholaminesmentioning
confidence: 99%
“…Besides a regulatory role in the "fight or flight" reflex, catecholamines also affect pro-and anti-inflammatory responses in immune cells and peripheral tissues, mediated by the variety and bioavailability of adrenergic and dopaminergic receptors [2][3][4]. For example, adrenergic proand anti-inflammatory signaling is dependent on the abundance of a and b receptors [5,6]. Besides adrenergic signaling, recent studies have underscored the importance of dopaminergic pathways in moderating inflammatory conditions in experimental models of organ injury [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TH is also expressed in non-neuronal cells such as lymphocytes, macrophages and other immune cells (25, 38). Similarly, it has been reported that synapsin is also found in some non-neuronal cells (e.g., osteoblasts (39) insulinoma cells (40), epithelial cells (41)), but it has not been reported in vascular or immune cells.…”
Section: Discussionmentioning
confidence: 99%